1985
DOI: 10.1071/bi9850095
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of Nutrients in Merino Ewes. 11 Glucose Utilization by Skeletal Muscle, the Pregnant Uterus and the Lactating Mammary Gland in Relation to Whole Body Glucose Utilization

Abstract: The net uptake and oxidation of glucose by leg muscle, pregnant uterus, and lactating mammary gland, together with the rate of irreversible loss and oxidation of glucose in the whole body of Merino ewes are reported. The ewes were fed on either chaffed oaten hay (OR), chaffed lucerne hay (L), or a mixture of chaffed oaten and lucerne hays (OHL). Measurements were made during five different physiological states: dry (nonpregnant), at 94 and 125 days of pregnancy, and at 20 and 50 days after lambing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 29 publications
(48 reference statements)
0
24
0
1
Order By: Relevance
“…In this study whole body glucose utilization and both muscle and uterine glu¬ cose uptake was not significantly changed by neutrali¬ zation of oPL. This is not surprising in view of recent in-vivo studies of the ewe hind limb which have shown that muscle glucose uptake was unchanged (or even slightly increased) in pregnancy, relative to the nonpregnant state (Oddy et al 1985).…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…In this study whole body glucose utilization and both muscle and uterine glu¬ cose uptake was not significantly changed by neutrali¬ zation of oPL. This is not surprising in view of recent in-vivo studies of the ewe hind limb which have shown that muscle glucose uptake was unchanged (or even slightly increased) in pregnancy, relative to the nonpregnant state (Oddy et al 1985).…”
Section: Discussionmentioning
confidence: 47%
“…Weight of ewes, fetal weight and number, weight of uterine tissue and fluids, feed dry matter and estimated metabolizable energy (ME) intake of ewes in anti-ovine pla¬ cental lactogen (treated)-and normal globulin (untreated)- Dry feed intake (kg/day) 0-97 + 0-27 0-54 + 0-39 ME intake (MJ/day) 9-9 + 2-7 5-5 + 3-8 cose. With the infusion continuing, simultaneous measurements of blood-flow rate and sampling of blood for measurement of glucose and C02 specific radioactivity were made (Oddy, Gooden, Hough et al 1985). Blood was withdrawn continuously over 1 h (6 10 ml samples) at 1 ml/min from the femoral artery, femoral vein and utero-ovarian vein.…”
Section: Measurement Of the Antiserum Titrementioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps it is some other specific nutrient such as glucose which is known to be utilized by the follicle bulb (Leng & Stephenson, 1965) ? Although there is a significant decline in the amount of glucose available to maternal non-muscle tissues in pregnancy, no such decline occurs in lactation (Oddy et al 1985). Increased amino acid supply, in the form of formal-dehyde-treated casein (Barry, 1969;Henderson et al 1970) or infusion of casein into the abomasum (Williams etal.…”
Section: Discussionmentioning
confidence: 99%
“…In the present experiments, feed intakes were not different across pregnant and non-pregnant ewes and the constant infusion rates suggest similar total utilization rates, while the difference in MPII reflects different patterns of glucose utilization. Thus as pregnancy advances, the site of utilization changes, from peripheral tissues (muscle and adipose tissues) to the gravid uterus [13,56]. If there were no mechanisms in place to suppress peripheral glucose utilization, be it insulin resistance or reduced insulin output, it should be expected that pregnant animals would show a greater GIR and an increased MPII.…”
Section: Discussionmentioning
confidence: 99%